Economical and Morpho-Biological Features of Whiner Wheat New Generation Varieties (Triticum durum) - Л. І. Улич; С. М. Гринів; В. М. Лисікова; В. М. Матус (Plant Varieties Studying and Protection)
The article describes summary of the researches, characteristics of morphological and agro-biological characteristics and features, a note is made of a significant progress in the selection of productivity and adaptability of registered Durum Winter Wheat Varieties of new crops rotation. Significant developments of  plants architectonic are marked, especially in height, characteristics of economical value, and in terms of considerable achievements in breeding of this kind of wheat. A stress in made on the need to enhance Durum Winter Wheat breeding to develop more frostresistant and drought-overheat resistant varieties.